Genetic Attenuation of Paraoxonase 1 Activity Induces Proatherogenic Changes in Plasma Proteomes of Mice and Humans - Marta Sikora; Ewa Bretes; Joanna Perła-Kaján; Izabela Lewandowska; Łukasz Marczak; Hieronim Jakubowski (MDPI AG, 2020)
High-density lipoprotein (HDL), in addition to promoting reverse cholesterol transport, possesses anti-inflammatory, antioxidative, and antithrombotic activities. Paraoxonase 1 (PON1), carried on HDL in the blood, can contribute to these antiatherogenic activities. The PON1-Q192R polymorphism involves a change from glutamine (Q variant) to arginine (R variant) at position 192 of the PON1 protein and affects its enzymatic activity. The molecular basis of PON1 association with cardiovascular and neurological diseases is not fully understood. To get insight into the function of PON1 in human disease, we examined how genetic attenuation of PON1 levels/activity affect plasma proteomes of mice and humans. Healthy participants (48.9 years old, 50% women) were randomly recruited from the Poznań population. Four-month-old Pon1−/− (n = 17) and Pon1+/+ (n = 8) mice (50% female) were used in these experiments. Plasma proteomes were analyzed using label-free mass spectrometry. Bioinformatics analysis was carried out using the Ingenuity Pathway Analysis (IPA) resources. PON1-Q192R polymorphism and Pon1−/− genotype induced similar changes in plasma proteomes of humans and mice, respectively. The top molecular network, identified by IPA, affected by these changes involved proteins participating in lipoprotein metabolism. Other PON1 genotype-dependent proteomic changes affect different biological networks in humans and mice: "cardiovascular, neurological disease, organismal injury/abnormalities" in PON1-192QQ humans and "humoral immune response, inflammatory response, protein synthesis" and "cell-to-cell signaling/interaction, hematological system development/function, immune cell trafficking" in Pon1−/− mice. Our findings suggest that PON1 interacts with molecular pathways involved in lipoprotein metabolism, acute/inflammatory response, and complement/blood coagulation that are essential for blood homeostasis. Modulation of those interactions by the PON1 genotype can account for its association with cardiovascular and neurological diseases.